Hepatic-atrial shunt: a novel technique for suprahepatic inferior vena cava tumoral thrombus in hepatoblastoma - Ma. Alejandra Delgado C; Bruno Catoia F; Isabel Fuentealba T; Gloria González G (Elsevier, 2023)
ABSTRACT: Background and Aims: In unresectable, PostTEXT III and IV pediatric hepatic neoplasms, liver transplantation (LT) is the main curative option. The presence of a tumoral thrombus (TT) adds a significant challenge. Few reports have been published on how to solve suprahepatic inferior vena cava (IVC) TT in pediatric hepatoblastoma (HB). The aim of this study is to report an alternative surgical technique. Methods: We describe the surgical technique and review the demographic features, postoperative complications, and survival of two cases of HB with suprahepatic IVC-TT. Results: We report the surgical technique of LT, vena cava resection, and placement of a hepatic-atrial shunt (HAS) in 2 infants treated for high-risk HB, PostTEXT IV and III tumors, with suprahepatic IVC TT. Warm ischemia time was 43 and 46 minutes, hospital stay 60 and 47 days respectively. Histology showed negative margins. Both patients are disease-free without HAS-related complications at 32 and 30 months of follow-up. Conclusions: We present a novel surgical technique, allowing for successful LT. Since these patients had long-term total IVC occlusion, and developed collateral drainage veins, we considered replacement was not necessary. Further follow-up is needed to determine long-term surgical complications and event-free survival.